ECOLOGICALLY UNEQUAL EXCHANGE DAN PRODUKSI INSEKURITAS: ANALISIS ANCAMAN KEAMANAN MANUSIA DALAM PERDAGANGAN E-WASTE DI GHANA - Anggi Regina C; Fajar Imam Zarkasyi (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2026)
Abstract: The research findings show that ecological inequality in the e-waste trade operates as a mechanism for producing human insecurity. Through environmental cost-shifting, appropriation of environmental space, and underdevelopment, the ecological burden transferred to Ghana develops into a critical and pervasive threat to the human vital core, thereby disrupting the environmental security, health security, and economic security of local communities. Thus, the e-waste trade not only reproduces global ecological inequality, but also reproduces multidimensional insecurity at the human level. Keywords: e-waste; Ghana; Ecologically Unequal Exchange; Human Security; Multidimensional Insecurity   Abstrak: Temuan penelitian menunjukkan bahwa ketimpangan ekologis dalam perdagangan e-waste beroperasi sebagai mekanisme produksi insekuritas manusia. Melalui environmental cost-shifting, appropriation of environmental space, dan underdevelopment, beban ekologis yang dipindahkan ke Ghana berkembang menjadi ancaman yang bersifat critical adan pervasive terhadap vital core manusia sehingga mengganggu environmental security, health security, dan economic security masyarakat. Dengan demikian, perdagangan e-waste tidak hanya mereproduksi ketimpangan ekologis global, tetapi juga mereproduksi insekuritas multidimensional pada tingkat manusia. Kata kunci: Limbah Elektronik; Ghana; Ecologically Unequal Exchange; Keamanan Manusia; Ancaman Multidimensi